New record of Panulirus penicillatus (Olivier 1791) in the Southeastern Gulf of California, Mexico (Crustacea: Palinuridae) - Flores-Campaña, Luis Miguel (Universidad de Costa Rica, 1991)
Off Mazatlan, Sinaloa, Mexico. The present record confinns the presence of P. penicillatus on the continental margin o f Sinaloa.